2014
DOI: 10.1159/000367586
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Receptor-β Gene Reexpression and Biological Activity in SHI-1 Cells after Combined Treatment with 5-Aza-2′-Deoxycytidine and All-<b><i>Trans</i></b> Retinoic Acid

Abstract: Background: This study was conducted to determine the antineoplastic activities of 5-aza-2′-deoxycytidine (decitabine; DAC) and all-trans retinoic acid (ATRA), administered either alone or in combination, on in vitro cultured SHI-1 cells as well as their effects on the expression of the tumor suppressor gene p16INK4a (p16) and the retinoic acid receptor (RAR)-β. Methods: Cellgrowth inhibition, differentiation and apoptosis were determined in SHI-1 cells treated with DAC and/or ATRA, and the combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Previously, the present authors administered 15 mg/m 2 /day decitabine (days 1–5) combined with 20 mg/m 2 /day all-trans RA (days 1–28) to successfully treat 31 cases of myeloid neoplasms not suitable for intensive chemotherapy, with an ORR of 58.1% and a 2-year survival rate of 26.6%. 15 The side effects were mainly tolerable haematologic toxicities. In the present case, the same regimen was used to treat a patient diagnosed with PMF–tAML.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, the present authors administered 15 mg/m 2 /day decitabine (days 1–5) combined with 20 mg/m 2 /day all-trans RA (days 1–28) to successfully treat 31 cases of myeloid neoplasms not suitable for intensive chemotherapy, with an ORR of 58.1% and a 2-year survival rate of 26.6%. 15 The side effects were mainly tolerable haematologic toxicities. In the present case, the same regimen was used to treat a patient diagnosed with PMF–tAML.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] Previous studies found that all-trans RA plus decitabine could induce the apoptosis and differentiation of leukemia cell lines K562, SHI-1 and U937 via upregulation of RARb gene expression. 15,17,18 In clinical practice, the ORR to treatment with alltrans RA plus decitabine in patients with myeloid leukaemia who cannot tolerate strong chemotherapy is 58.1%, with a median overall survival of 11 months. 19 In the present case, the diagnosis of PMF transforming into AML in addition to complex karyotypes, predicted a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of the combination of effects of a methylating agent, such as 5-AZA-CdR with retinoids, has been explored in a number of different malignant and pre-neoplastic conditions [23][24][25]. The observation of loss of expression of some retinoid receptors by promoter methylation, associated with loss of retinoid sensitivity and thus retinoid-related modulation of differentiation and cell cycle arrest, indicates that this is potentially a useful concept for chemoprevention.…”
Section: Discussionmentioning
confidence: 99%
“…These agents, including 5-aza-2 -deoxycytidine (5-AZA-CdR), have been used clinically in the treatment of myelodysplastic syndromes and AML, where retinoid therapy is also employed. The effects of such combinations have been reported in vitro and in vivo clinical studies, with promising effects [23,24]. The approach has also been assessed in solid tumours, such as breast carcinoma and neuroblastoma [25,26].…”
Section: Introductionmentioning
confidence: 99%